Analysis of the Gale in the Bohai Sea Caused by Tropical Cyclone “Yagi” - Tiantian Hu; Binxian Liu; Di Wu; Xiaoyuan Yi (Advances in Meteorology)
In this study, we analyzed the meteorological processes associated with 2018 tropical cyclone No. 14, “Yagi.” TC Yagi continued moving northeastward after losing its numerical designation from the National Meteorological Center of the China Meteorological Administration (CMA) because of weakening and then restrengthened when it moved over the Bohai Sea, inducing an ocean gale on 14-15 August 2018. The results of our investigation revealed that the continued northeastward movement of Yagi on 14 August was related to the divergence of the upper-level westerly jet stream, the northward shift of the subtropical high in the midtroposphere, as well as the steering flow and asymmetrical air flow around the disturbance itself in the lower troposphere. The enhancement of Yagi over the Bohai Sea on the night of 14 August was related to the decrease of friction over the ocean and the increase of diabatic heating from the sea surface flux. The wind speed increased to a maximum when the depression moved over the Bohai Sea, an occurrence that was not only due to the enhancement of the cyclone itself but also due to the flow of cold air from high latitudes along the north side of the Bohai Sea. The behavior of the cold air was related to the shift of the convergence zone in the upper-level westerly jet at 200 hPa, long-wave troughs and ridges at 500 hPa, and terrain effects. Thus, the gale development in the Bohai Sea was due to both the enhancement of tropical cyclone Yagi after it moved over the ocean and the flow of cold air from high latitudes.